Sustainability initiatives for green tourism development: The case of Wayanad, India - Nimi Markose; V. T. Bindu; Babu George (Journal of Risk and Financial Management, 2022)
Mainstream sustainability discussions draw focus to the balance between commercial and environmental interests. Responsible tourism (RT) practices are an outcome of these discussions and RT is a significant contributor to the 'greenification' of economies in many countries. Green tourism promotes travel that supports natural and cultural aspirations, while also supporting protection of the destination community's limited resources. Kerala, India, is a pioneer in implementing RT. The present study exploratively analyzes the RT initiatives at different phases, especially within the lens of sustainable responsible tourism initiatives for green tourism development. The research is descriptive in nature and is guided by the bottom line approach (TBL) for green economic development. The findings highlight the dynamics of challenges experienced in the different phases of RT implementation. Based on our analysis of the secondary data, the first phase implementation of RT was not very successful; the second and the third phases seemed to be more promising. The study also throws light on the need for future studies in other culturally distant destinations; this will result in promising practices being adopted as alternative strategies for sustainable tourism development globally.
Keywords: 330; responsible tourism; sustainability; green tourism development; triple bottom line approach; Kerala; India